Faktor-faktor yang berhubungan dengan keluhan pernapasan pada petugas penyapu jalan - Leony Shadira; Fajrina Hidayati; Oka lesmana; Adelina Fitri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Data from the 2023 Indonesian Health Survey (SKI) showed a prevalence of 887,531 respiratory tract infections in Indonesia, while in Jambi Province the prevalence was 11,588 cases. According to data from the Indonesian Ministry of Health in 2024, four of the ten most common diseases are related to the respiratory system: COPD, lung cancer, pneumonia, and asthma. Upper respiratory tract infections are infectious diseases that infect the initial part of the respiratory tract, from the nose to the alveoli, as well as structures such as the sinuses, middle ear cavity, and pleura. Purpose: To determine factors associated with respiratory complaints in street sweepers. Method: This quantitative study used a cross-sectional design. The sampling technique used was random sampling, so that the entire population meeting the inclusion criteria, totaling 84 respondents, was selected as the study sample. Data collection was conducted using a questionnaire through direct interviews and analyzed univariately and bivariately using the chi-square test. Results: Bivariate analysis showed a significant relationship between respiratory complaints in street sweepers with gender (p value = 0.007; PR 0.44; 95%CI 0.24-0.76), smoking habits (p value = 0.020; PR 0.521; 95%CI 1.128-3.377), and use of personal protective equipment (p-value = 0.032; PR 1.46; 95%CI 0.30-0.94). There was no significant relationship between respiratory complaints in street sweepers with age (p-value = 0.313; PR 0.21; 95%CI 0.58-7.65), and length of service (p value = 0.127; PR 0.625; 95%CI 0.354-1.104). Conclusion: Gender, smoking habits, and use of PPE are associated with respiratory complaints in street sweepers.   Keywords:  Respiratory Complaints, Street Sweeper